If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-5 + -1) + -2f = -2(3 + -5) Combine like terms: -5 + -1 = -6 (-6) + -2f = -2(3 + -5) -6 + -2f = -2(3 + -5) Combine like terms: 3 + -5 = -2 -6 + -2f = -2(-2) Multiply -2 * -2 -6 + -2f = 4 Solving -6 + -2f = 4 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -2f = 4 + 6 Combine like terms: -6 + 6 = 0 0 + -2f = 4 + 6 -2f = 4 + 6 Combine like terms: 4 + 6 = 10 -2f = 10 Divide each side by '-2'. f = -5 Simplifying f = -5
| (5x-7)(7x+9)=0 | | -100(x+4)+54=-13-13 | | 5(x-2)=-9(x+1)+17 | | 12/21=18/x | | 66+30x=360+30x | | (5x+5)(5x^2+3x+2)= | | 3(4z+3)= | | -3(7.5+-3y)-2y=5.5 | | 6/5 | | 23-13=2(x-8) | | 4d-5(d-1)=3-d+2 | | 3p+5=p+15 | | 6/7(-4/9-1/7x)=-62/147 | | X=3-12 | | -12y+10=46 | | 5+7x+16+x=11x-3-x | | 6k+5=20 | | 9y^2-12y-1=0 | | h(t)=20-16t*2+32t | | 12s=8+2x(5s+3) | | 5(x-4)=-7(x+3)+45 | | 11x^2(144)=0 | | 3j^2-20j=12 | | 2x-9+87-9x*9+1=100 | | 9x*lnx+x=0 | | 27=3d | | 12s=8+10s+6 | | x^2+10x+14=8 | | 11x^2-55x=0 | | (2x^2-4y)dx+(-4x-y^4)dy=0 | | 5(2x+4)=37 | | 25=2h+5 |